2017
DOI: 10.1007/s12020-017-1494-z
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and bone effects of high-fat diet in adult zebrafish

Abstract: An increase of visceral fat affects human bone health causing fragility, mechanical strength reduction, and increased propensity to fractures because of impaired bone matrix microstructure and aberrant bone cell function. Adult Danio rerio (zebrafish) represents a powerful model to study both metabolic diseases and bone metabolism. The aim of this study was to generate an obese adult zebrafish by high-fat diet and evaluate metabolic and bone tissue effects. Fish blood glucose and insulin levels were found to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 37 publications
3
36
0
Order By: Relevance
“…Rb1 reduced the triglyceride accumulation in 3T3‐L1 adipocytes (Park et al, 2008). We used high‐cholesterol diet adult zebrafish possessing structural and functional similarities with humans of obesity to determine the antihyperlipidemia effects of Rb1 in vivo (Carnovali, Luzi, Terruzzi, Banfi, & Mariotti, 2018; Chen, Zheng, & Zhang, 2018; Holtta‐Vuori et al, 2010; Ma et al, 2019). In the present study, 10 adult zebrafish were used to measure TC and TG levels, which were quantified using a measurement assay and the following groups were compared: HC group, simvastatin group (Sim), 25 μg/g (LF), 50 μg/g (MF), and 100 μg/g Rb1 (HF) group.…”
Section: Resultsmentioning
confidence: 99%
“…Rb1 reduced the triglyceride accumulation in 3T3‐L1 adipocytes (Park et al, 2008). We used high‐cholesterol diet adult zebrafish possessing structural and functional similarities with humans of obesity to determine the antihyperlipidemia effects of Rb1 in vivo (Carnovali, Luzi, Terruzzi, Banfi, & Mariotti, 2018; Chen, Zheng, & Zhang, 2018; Holtta‐Vuori et al, 2010; Ma et al, 2019). In the present study, 10 adult zebrafish were used to measure TC and TG levels, which were quantified using a measurement assay and the following groups were compared: HC group, simvastatin group (Sim), 25 μg/g (LF), 50 μg/g (MF), and 100 μg/g Rb1 (HF) group.…”
Section: Resultsmentioning
confidence: 99%
“…Several data are present in the literature on the fish oral cavity morphology (for review, see Kapoor & Khanna, 1994), and several evidences are present regarding the strict connection among the different manners of prehension, oral transport, mixing and swallowing, the feeding habits and the oral cavity morphology. An important role by different hormones in feeding, related to the morphological characteristics, has been recently demonstrated in the digestive system in teleosts (Audira et al, 2018;Carnovali, Luzi, Terruzzi, Banfi, & Mariotti, 2018;Mania et al, 2017;Montalbano et al, 2016Montalbano et al, , 2018. The most of the functional processes inside the oral cavity are carried out by the tongue, whose presence and description have been showed in different species of fish, demonstrating the variation in the presence of anatomical structures like taste buds, mucous cells and teeth in teleosts, also of commercial interest (Abbate et al, 2006(Abbate et al, ,2017(Abbate et al, ,2020a(Abbate et al, ,2020bAbbate, Guerrera, Montalbano, De Carlos, et al, 2012;Alsafy, Bassuoni, & Hanafy, 2018;Amato et al, 2012;Dos Santos, Arantes, Santiago, & Dos Santos, 2015;El Bakary, 2014;Elgendy, Alsafy, & Tanekhy, 2016;Germanà et al, 2009;Guerrera et al, 2015;Ikpegbu, Ibe, & Nlebedum, 2019;Kasumyan, 2019;Kettratad, Senarat, Boonyoung, & Jiraungkoorsku, 2017;Levanti et al, 2017;Mahmoud, Essa, & Sayed, 2016;Sadeghinezhad, Rahmatiholasoo, Fayyaz, & Zargar, 2015;Sayed, Mahmoud, & Essa, 2019;Yu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Similar concerns regarding nutritional requirements and diet standardization were addressed in rodent models several decades ago, leading to the development and adoption of standardized reference and open formulation diets of specific composition. 11 As observed in mammals, specific nutrients and dietary ingredients, or the lack thereof, can potentially alter physiology, behavior, and/or molecular pathways in zebrafish, [12][13][14][15][16][17][18][19][20][21][22][23][24][25] whereas other researches suggested that nutrient content of diets fed to adult zebrafish can even influence the development and health of their offspring. [26][27][28][29][30][31] All these evidences suggest that for zebrafish, diet is an important environmental factor that can potentially compromise and confound outcomes related to the question of study; Therefore, a lack of nutritional control in zebrafish laboratories could affect the interpretation of both past and future research.…”
Section: Introductionmentioning
confidence: 99%